Concentrate and degrade PFOA with a photo-regenerable composite of In-doped TNTs@AC. (August 2022) - Arana Juve, Jan-Max; Li, Fan; Zhu, Yangmo; Liu, Wen; Ottosen, Lars D.M.; Zhao, Dongye; Wei, Zongsu
Abstract: "Concentrate-and-degrade" is an effective strategy to promote mass transfer and degradation of pollutants in photocatalytic systems, yet suitable and cost-effective photocatalysts are required to practice the new concept. In this study, we doped a post-transition metal of Indium (In) on a novel composite adsorptive photocatalyst, activated carbon-supported titanate nanotubes (TNTs@AC), to effectively degrade perfluorooctanoic acid (PFOA). In/TNTs@AC exhibited both excellent PFOA adsorption (>99% in 30 min) and photodegradation (>99% in 4 h) under optimal conditions (25 °C, pH 7, 1 atm, 1 g/L catalyst, 0.1 mg/L PFOA, 254 nm). The heterojunction structure of the composite facilitated a cooperative adsorption mode of PFOA, i.e., binding of the carboxylic head group of PFOA to the metal oxide and attachment of the hydrophobic tail to AC. The resulting side-on adsorption mode facilitates the electron ( e ‒ ) transfer from the carboxylic head to the photogenerated hole ( h + ), which was the major oxidant verified by scavenger tests. Furthermore, the presence of In enables direct electron transfer and facilitates the subsequent stepwise defluorination. Finally, In/TNTs@AC was amenable to repeated uses in four consecutive adsorption-photodegradation runs. The findings showed that adsorptive photocatalysts can be prepared by hybridization of carbon and photoactive semiconductors and the enabled "concentrate-and-degrade" strategy is promising for the removal and degradation of trace levels of PFOA from polluted waters. Graphical abstract: Image 1 Highlights: Adsorptive photocatalyst (In/TNT@AC) was prepared to concentrate-and-degrade PFOA. In/TNT@AC can adsorb PFOA from water and degrade it under UV irradiation. 2% Indium dopant enhanced adsorption and subsequent solid-phase degradation of PFOA. In promotes direct electron transfer from PFOA to the photogenerated hole ( h + ). The photodegradation also regenerates In/TNT@AC, allowing for repeated uses.